On the local limit theorem for the densities in the space R^k - Saulis, L. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. Саулис. О локальной предельной теореме для плотности распределения в R^kL. Saulis. Apie paskirstymo tankių erdvėje R^k ribinę lokalinę teoremą